Pengaruh Edukasi Bahan dan Urgensi Penekanan Waktu terhadap Keputusan Pembelian Skincare "Sofia Skin Solution" pada Live Commerce dimediasi Perceived Value - Shofiyah; Prasetiyo, Andri; Ahmar, Nurmala; Wirabrata, I Gede Made (PendIPA Journal of Science Education, 2025)
Live streaming is changing the digital marketing landscape, especially in the skincare industry. This research aims to examine the influence of ingredients education and time pressure on consumer purchasing decisions on “Sofia Skin Solution” products, with perceived value as a mediating variable. The research was conducted with a quantitative approach through a survey of 200 respondents active in the live streaming session. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Results showed that ingredient education positively influenced perceived value (T-value = 6.104; p = 0.000), as did time pressure (T-value = 6.339; p = 0.000), with time pressure showing a slightly more dominant influence. Perceived value alone exerted the strongest influence on purchasing decisions (T-value = 5.512; p = 0.000), and was shown to fully mediate the relationship between ingredient education and purchasing decisions, as well as partially mediating the influence of time pressure on purchasing decisions. The direct effect of content education on purchasing decisions is not statistically significant, but is at the threshold, which crucially indicates the role of other factors such as brand image and host credibility. Findings confirm the importance of live streaming scripts that balance concise product information with short promotions to build trust and enthusiasm. Managerial implications suggest companies design short ingredient demonstrations followed by short offers to maximize conversions on live commerce platforms.